2020
DOI: 10.1017/s0950268820002204
|View full text |Cite
|
Sign up to set email alerts
|

Public attitude towards quarantine during the COVID-19 outbreak

Abstract: Due to the outbreak of the deadly coronavirus disease in 2019 (COVID-19), Wuhan was on lockdown for more than 60 days by the state government. This study investigated the perceptions and attitudes of the public on quarantine as a practical approach to halting the spread of COVID-19. An online survey was conducted via WeChat between 10 January 2020 and 10 March 2020 on the general population in Hubei province at the height of the COVID-19 outbreak. In total, 549 respondents participated in the survey. Results r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…According to the following statistics, quarantine is considered a viable solution to the epidemic of infectious diseases: 65% in India, 28 94% Canada, 19 89% in Singapore, 95% in Taiwan, 76% in the United States 32 and 92% in China. 33 These results support the findings of this study, 91% of the participants believed that quarantine is the best way to prevent infectious diseases. In the current study, age and education had a significant relationship with attitudes towards quarantine, in order that with increasing age and level of education of participants, their attitudes towards quarantine decreased.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…According to the following statistics, quarantine is considered a viable solution to the epidemic of infectious diseases: 65% in India, 28 94% Canada, 19 89% in Singapore, 95% in Taiwan, 76% in the United States 32 and 92% in China. 33 These results support the findings of this study, 91% of the participants believed that quarantine is the best way to prevent infectious diseases. In the current study, age and education had a significant relationship with attitudes towards quarantine, in order that with increasing age and level of education of participants, their attitudes towards quarantine decreased.…”
Section: Discussionsupporting
confidence: 88%
“…However, there are differences in age, Tracy et al stated that their participants have a more positive attitude towards quarantine with ageing, while in the Song et al study, similar to the findings of the present study, reported a lower attitude with increasing age. 19 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…This indicated the concerns and support of techno experts and directions to the patients in following the precautions by themselves for their fast recovery. Song et al ( 2020 ) have also exerted the public's supportive attitude toward home quarantine and following other necessary protocols, keeping in mind the nation's larger interest. It has also been observed that India's higher tendency to conform to rules and formal obligations that are considered important for the larger group (Bandyopadhyay and Fraccastoro, 2007 ) might have also impacted these behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…These ndings suggest that interventions, such as isolation and quarantine, can effectively reduce the peak number of COVID-19 infection cases and delay infection cases' peak time by reducing the contact rate [30]. Another study showed that the infection's epidemic trend mainly depends on quarantine and suspected cases [31].…”
Section: Discussionmentioning
confidence: 97%
“…Worldwide, it appeared easier to stay in social isolation during the early stage of COVID-19 spread. During the initial months of the quarantine, a study conducted in China reported that the public displayed signi cantly strong support toward quarantine measures throughout the outbreak period, except for locking people up and using imprisonment or other legal sanctions against those who failed to comply with the stringent regulations [31]. However, over the months of 2020, maintaining strict isolation and avoiding large gatherings and events was increasingly complex, and people were more reluctant to follow social distancing measures.…”
Section: Discussionmentioning
confidence: 99%